An Empirical Investigation of the Impact of Human Resource Outcomes on Organizational Performance in Small and Medium Scale Manufacturing Firms in Sri Lanka. - Weerakkody, W. A. S. (8th International Conference on Business & Information ICBI – 2017, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka., 2017)
The main objective of this study was to investigate the relationship between HR Outcomes and organizational performance of small and medium scale manufacturing firms in Sri Lanka. The research framework consists of two independent variables namely employee attitudes, behaviors, and the dependent variable. Two hypotheses were formulated using deductive approach to be tested under this study. Variables are neither manipulated nor controlled for the study. Hence, the study was conducted in a non-contrived setting. As the data for this study were collected at a single point in time, the study was cross-sectional in time horizon. Measures of the study had possessed sufficient validity and reliability. The sample for this study was selected from the Export Development Board (EDB) and Ministry of Industrial Development (MID). The structured questionnaire, which consists of 208 statements with seven-point scale, was used in order to collect the data and the sample consisted of 150 small and medium enterprises Sri Lanka. Hence, the unit of analysis was at the firm level. The researcher used Convenient Judgmental and Quota method to select the sample CEOs/ HR managers/owner managers/ MDs gave information on behalf of the firms. The data analysis included the univariate, bivariate, and multivariate analysis. The findings revealed that there are positive relationships between HR Outcomes and organizational performance. It is concluded that there is a positive and relatively weak relationship between HR outcomes and organizational performance in small and medium enterprises in Sri Lanka.
Keywords: Employee attitudes; Employee Behavior; Human Resource Outcomes; Organizational Performance; Small and medium Scale Businesses